Potential U.S. Production of Liquid Hydrocarbons From Biomass With Addition of Massive External Heat and Hydrogen Inputs - T. W. Charlton; C. W. Forsberg; B. E. Dale (GCB Bioenergy)
ABSTRACT We estimate the U.S. potential to convert biomass into liquid hydrocarbons for fuel and chemical feedstocks, assuming massive low‐carbon external heat and hydrogen inputs. The biomass is first a carbon feedstock and only secondarily an energy source. This analysis is done for three estimates of available biomass derived from the 2023 U.S. Department of Energy/U.S. Department of Agriculture “Billion‐Ton Report” and two augmented cases with maximum annual production of 1326, 4791, 5799, 7432, and 8745 million barrels of diesel fuel equivalent per year for the five cases. Constraints, such as assuring long‐term soil sustainability by recycling nutrients and some carbon back to soils, result in production being 70%–80% of these numbers. The U.S. currently consumes about 6900 million barrels of diesel fuel equivalent per year. Long‐term estimates for U.S. hydrocarbon consumption are between 50% and 75% of current consumption. External hydrogen additions for the conversion processes in the five cases are, respectively 25, 91, 111, 142, and 167 million tons of hydrogen per year. The system is strongly carbon negative because of carbon and nutrient recycling to soils to improve soil productivity.